Changes in health-related quality of life are associated with patient satisfaction following total hip replacement: an analysis of 69, 083 patients in the Swedish Hip Arthroplasty Register. (2nd January 2020) - Ray, Gabrielle S; Ekelund, Philip; Nemes, Szilard; Rolfson, Ola; Mohaddes, Maziar
Abstract : Background and purpose — Total hip replacement (THR) aims mainly to improve quality of life via restoration of hip function and provision of pain relief. This study sought to assess whether improvements in quality of life between the preoperative and 1-year postoperative period were associated with patient satisfaction Patients and methods — Data were extracted for 69, 083 THR operations with complete data reported to the Swedish Hip Arthroplasty Register (SHAR) between 2008 and 2015. Health-related quality of life and patient satisfaction were captured using the Euro-Qol-5D (EQ-5D) and visual analogue scale (VAS), respectively. Multivariable analysis was performed to assess associations between the changes in pre- and postoperative EQ5D and patient satisfaction. Results — In patients reporting severe or moderate problems with mobility preoperatively, improvement to no problems was associated with numerically higher patient satisfaction (coefficient –18 [95% CI –22 to –14] and –18 [–18 to –17]). Improvement in the self-care dimension from severe or moderate problems to no problems was associated with numerically higher patient satisfaction (–15 [–16 to –14] and –13 [–15 to –11]). Improvement from severe problems with the ability to perform usual activities to no problems was associated with numerically higher patient satisfaction (–18 [–19 to –17]). This association was also found for improvement in pain/discomfort and anxiety/depression (–16 [–17 to –15] and –15 [–16 to –14]). Interpretation — Our results indicate that satisfaction with the operated hip is a valid patient-reported outcome reflecting the changes in different EQ-5D dimensions and should be included in the follow-up of patients after THR surgery.